Analisis Efektivitas Model Manajemen Kelas Demokratis terhadap Motivasi Belajar Siswa Sekolah Dasar Negeri 3 Jambu (Jurnal Motivasi Pendidikan dan Bahasa, 2025)
This study examines the effectiveness of implementing a democratic classroom management model in enhancing student learning motivation at Jambu Public Elementary School 3. A descriptive qualitative approach was employed, with data collected through direct classroom observations and interviews involving teachers and students. The aim was to understand how democratic principles applied in classroom settings could influence students’ motivation, behavior, and engagement in learning activities. The findings reveal that adopting democratic leadership in classroom management creates an inclusive, respectful, and participatory learning environment. Students are encouraged to express opinions, collaborate in decision-making, and take ownership of their learning process. This approach significantly enhances intrinsic motivation, responsibility, and student independence. It also helps reduce passive behavior and fosters a sense of belonging and self-worth among students. The results are in line with several prominent educational theories. According to Self-Determination Theory (Deci & Ryan), autonomy and relatedness are key drivers of motivation, which are facilitated through democratic practices. Vygotsky’s Social Development Theory emphasizes the role of social interaction in learning, which is actively promoted in this model. Carl Rogers’ humanistic approach also supports the creation of a learning climate centered on empathy and student potential, while Rudolf Dreikurs’ Adlerian classroom model advocates for respectful teacher-student relationships and cooperative behavior. Overall, the implementation of a democratic classroom management model is considered effective in promoting both academic achievement and character development at the elementary level. The study recommends broader application of this model in primary education settings to support holistic student growth and to foster a learning culture rooted in mutual respect, responsibility, and student agency.